Biomimetic Material for Quantification of Methotrexate Using Sensor Based on Molecularly Imprinted Polypyrrole Film and MWCNT/GCE - Jara-Cornejo, Eduardo (2023)
This study investigates biomimetic sensors for the detection of methotrexate contaminants in environmental samples. Sensors inspired by biological systems are the focus of this biomimetic strategy. Methotrexate is an antimetabolite that is widely used for the treatment of cancer and autoimmune diseases. Due to the widespread use of methotrexate and its rampant disposal into the environment, the residues of this drug are regarded as an emerging contaminant of huge concern, considering that exposure to the contaminant has been found to lead to the inhibition of some essential metabolic processes, posing serious risks to humans and other living beings. In this context, this work aims to quantify methotrexate through the application of a highly efficient biomimetic electrochemical sensor constructed using polypyrrole−based molecularly imprinted polymer (MIP) electrodeposited by cyclic voltammetry on a glassy carbon electrode (GCE) modified with multi−walled carbon nanotubes (MWCNT). The electrodeposited polymeric films were characterized by infrared spectrometry (FTIR), scanning electron microscopy (SEM), and cyclic voltammetry (CV). The analyses conducted using differential pulse voltammetry (DPV) yielded a detection limit of 2.7 × 10−9 mol L−1 for methotrexate, a linear range of 0.01–125 μmol L−1, and a sensitivity of 0.152 μA L mol−1. The results obtained from the analysis of the selectivity of the proposed sensor through the incorporation of interferents in the standard solution pointed to an electrochemical signal decay of only 15.4%. The findings of this study show that the proposed sensor is highly promising and suitable for use in the quantification of methotrexate in environmental samples.